Deconvolution approach to ultrasound medical imaging. - Ling, Mei Jun. (2009)
The aim of this work is to derive new algorithms for improving the spatial resolution of medical ultrasonic images and suppressing the speckle pattern. The project was oriented at 1-D and 2-D deconvolution using Wiener filter. An essential part of the task was to estimate the Point Spread Function (PSF) of the imaging process in the raw radio-frequency (RF) signal domain.